Systematic Literature Review: Kompetensi Manajerial dan Supervisi Akademik Kepala Sekolah Terhadap Kinerja Guru Taman Kanak-Kanak - Fitriyanti Fitriyanti (Journal of Innovation in Teaching and Instructional Media, 2025)
This article analyzed the managerial competence and academic supervision activities of kindergarten principals in relation to teacher performance. The study employs a Systematic Literature Review (SLR) approach by examining fifteen scientific articles published between 2018 and 2025. This method was applied to identify, select, and review relevant studies. The findings indicate that school leadership supported by strong managerial competence and effective academic supervision contributes significantly to improving the performance of kindergarten teachers. Therefore, enhancing the quality of principal leadership through training programs and supportive policies is a crucial factor in advancing the quality of early childhood education. This article is expected to provide both theoretical and practical contributions to strengthening the managerial competence of school principals and improving the effectiveness of academic supervision in order to support the optimization of kindergarten teacher performance.